The Influence of Leadership and Compensation on Employee Performance at PT REX Denpasar with Job Satisfaction as a Mediating Variable - Ni Luh Suastini; I Nengah Landra; I Nengah Suardika (International Journal of Economics and Management Sciences, 2025)
Human resources (HR) are a crucial component of any organization, playing a vital role in determining its development and success. One key aspect of HR management is employee performance, which reflects the quality and quantity of employee output in meeting company targets. This study focuses on PT REX Denpasar, a logistics company that experienced fluctuations in monthly revenue throughout 2023. This phenomenon indicates performance issues related to work quantity, delivery accuracy, and time efficiency. Several operational issues identified included variability in staff productivity, delays in delivery schedules, and inaccuracies in shipping data processing. To explore solutions to these challenges, the study examined the role of managerial leadership and financial incentives in improving employee performance, with job satisfaction as a mediating variable. This study covered all 40 employees of PT REX Denpasar, using a comprehensive enumeration sampling method. Data were collected through structured questionnaires, in-depth interviews, and a review of organizational records. Analysis was conducted using a structural path modeling approach to examine the relationships between variables. The results showed that managerial leadership had a significant effect on job satisfaction, as did the financial incentives provided by the company. Furthermore, leadership quality and compensation systems have been shown to have a positive correlation with improved employee performance. Furthermore, job satisfaction was found to act as a substantial mediator, strengthening the influence of leadership and compensation on performance. Thus, improving leadership quality and improving compensation mechanisms not only have a direct impact but also an indirect impact through increased job satisfaction.